2018
DOI: 10.1002/2017jb014265
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Evolution of Earthquake Dynamics: Case Study of the Mw 8.3 Illapel Earthquake, Chile

Abstract: We develop a methodology that combines compressive sensing backprojection (CS‐BP) and source spectral analysis of teleseismic P waves to provide metrics relevant to earthquake dynamics of large events. We improve the CS‐BP method by an autoadaptive source grid refinement as well as a reference source adjustment technique to gain better spatial and temporal resolution of the locations of the radiated bursts. We also use a two‐step source spectral analysis based on (i) simple theoretical Green's functions that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 114 publications
(192 reference statements)
3
13
0
Order By: Relevance
“…McFadden et al 1986) was used to enhance the signalto-noise ratio of the image, and the data were filtered in the 0. the kinematic BP and HBP methods. The source models of the 2015 Illapel earthquake showed a complex rupture evolution along both the up-dip and down-dip directions (Melgar et al 2016;An et al 2017;Yin et al 2018;Meng et al 2018), which is more consistent with the image obtained by the kinematic BP and HBP methods. The increased signal in the shallow part should reflect the source of high-frequency radiation from the up-dip rupture propagation.…”
Section: Application To the Real Datasupporting
confidence: 81%
“…McFadden et al 1986) was used to enhance the signalto-noise ratio of the image, and the data were filtered in the 0. the kinematic BP and HBP methods. The source models of the 2015 Illapel earthquake showed a complex rupture evolution along both the up-dip and down-dip directions (Melgar et al 2016;An et al 2017;Yin et al 2018;Meng et al 2018), which is more consistent with the image obtained by the kinematic BP and HBP methods. The increased signal in the shallow part should reflect the source of high-frequency radiation from the up-dip rupture propagation.…”
Section: Application To the Real Datasupporting
confidence: 81%
“…An event with elevated scaled energy radiates more high‐frequency ground motions given its size, and vice versa—one that is depleted in high‐frequency seismic waves is found inefficient at radiating seismic waves (Baltay et al, ). An appropriate metric to quantify the temporal evolution of high‐frequency radiation is seismic power, sometimes referred to as radiated energy rate (Ide et al, ; Yabe & Ide, ; Yin et al, ), which is simply proportional to the square of moment acceleration, ĖRfalse(tfalse)=()115πρα5+110normalπρβ5trueM¨02false(tfalse), where the density is ρ , the P wave speed is α , and the S wave speed is β , commonly assumed to be homogeneous near the source. An additional metric I propose to use aims to compare energy with moment throughout the rupture, which I refer to as the time‐dependent scaled energy, ESfalse(tfalse)=ERfalse(tfalse)false/M0false(tfalse). …”
Section: Moment Rate Seismic Power and Scaled Energy Functionsmentioning
confidence: 99%
“…An event with elevated scaled energy radiates more high-frequency ground motions given its size, and vice versa-one that is depleted in high-frequency seismic waves is found inefficient at radiating seismic waves (Baltay et al, 2011). An appropriate metric to quantify the temporal evolution of high-frequency radiation is seismic power, sometimes referred to as radiated energy rate (Ide et al, 2008;Yabe & Ide, 2014;Yin et al, 2018), which is simply proportional to the square of moment acceleration,…”
Section: Moment Rate Seismic Power and Scaled Energy Functionsmentioning
confidence: 99%
“…The high-frequency falloff rate of source spectra has been inferred to vary along dip of subduction zones [Ye et al, 2016]. In addition to this observation, several studies have indicated that low frequency radiation is promoted up-dip of faults in contrast to highfrequency radiation that is mostly representative of the down-dip excitation [Yao et al, 2011;Meng et al, 2011;Yin et al, 2018]. Dynamic models of subduction-zone earthquakes also predict its along-dip variation [Huang et al, 2013;Kozdon and Dunham, 2013;Ma and Hirakawa, 2013;Galvez et al, 2014] where the slip-rate function in the down-dip part is enriched in high-frequencies compared to the shallow slip-rate functions.…”
Section: Introductionmentioning
confidence: 97%
“…Radiated energy rate has been used to quantify the low but spatially heterogeneous seismic efficiency of tectonic tremor [Ide et al, 2008;Yabe and Ide, 2014]. Estimates of radiated energy rate for large teleseismic earthquakes have been proposed by Poli and Prieto [2016], through removal of theoretical attenuation model, and by Denolle et al [2015] and Yin et al [2018] through removal of eGfs. This study serves as a retrospective analysis of the work of Denolle et al [2015] and Yin et al [2018].…”
Section: Introductionmentioning
confidence: 99%